Particle Flow Simulation of Failure Characteristics of Deep Rock Influenced by Sample Height-to-Width Ratios and Initial Stress Level under True-Triaxial Unloading - Haoyu Rong; Guichen Li; Jiahui Xu; Ruiyang Bi; Yuantian Sun; Yaqiao Hu; Guoliang Bai (Geofluids)
The micromechanism of the effects of different height/width ratios (H/W) and initial stress levels on unloading characteristics of deep rock was investigated based on PFC3D true-triaxial unloading simulation. The results show that the increase of H/W will increase the movement speed of rock particles and intensify the acoustic emission (AE) activity inside the rock. With the increase of H/W, the failure mode of rock changes from splitting failure to tensile-shear failure. With increasing initial stress level, the particle velocity and overall fragmentation degree of rock increase. However, the increase of lateral stress will limit the coalescence of microfractures and weaken AE activity in the rock. Under unloading condition, the bonds between particles generally crack along the unloading direction, and the tensile effect is more pronounced under the condition of low initial stress level and high H/W. Under unloading condition, the variable energy of rock increases with increasing H/W and initial stress level, and the kinetic energy of rock particles increases with increasing H/W. The increase of initial stress level will increase the kinetic energy of rock particles when H/W is high.